Assessment of Antioxidant, Antidiabetic, Antidiarrheal, Analgesic and Antipyretic Activities and Phytochemical Screening on Different Fractional Methanolic Extract of Ampelocissus barbata (Wall.) Planch Fruits - Islam, Shahenul; Sultana, Sabrina; Islam, Mohammad Mimkul; Binty, Badrunnahar; Hossan, Nazmul; Mahmud , Hasan; Hossain, Md Akbar (Bangladesh Pharmaceutical Journal, 2026)
Ampelocissus barbata is a natural medicinal herb, regionally known as ‘Jarila Lahari’. This research sought to examine the fruits of A. barbata for their phytochemical screening, analgesic, antipyretic, antidiarrheal, antidiabetic, and antioxidant properties. To determine the activities, the methanolic crude extract (CE), as well as ethyl acetate (EAF), carbon tetrachloride (CTF), chloroform (CF) and petroleum ether (PEF) soluble fractions of A. barbata fruits were evaluated using recognized chemical techniques. Alkaloids, tannins, flavonoids, terpenoids, glycosides, saponins, proteins, and xanthoproteins were identified in the extract. In the DPPH assay, the crude extract and the pet. ether fraction showed very strong IC50 values of about 14.832 µg/ml and 23.87 µg/ml, accordingly. The raw sample and pet. ether fraction showed significant values of approximately IC50 (36.83 µg/ml and 24.46 µg/ml), SC50 (42.29 µg/ml and 29.2 µg/ml) and SC50 (38.13 mg/l and 39.17 mg/l), significantly, in the NO• scavenging activity, hydrogen peroxide scavenging assay, and hydroxyl radical assay. In the antidiabetic test, both BGL (500 mg/kg) and BGL (250 mg/kg) demonstrated a notable decline in blood sugar levels at 60 and 90 minutes. Strong antidiarrheal action was shown by the extract, which decreased diarrheal episodes by 82.96% & 87.4% and decreased the writhing response in the analgesic test by 78% and 73% at 250 mg/kg and 500 mg/kg accordingly. It exhibited a statistically prominent (p < 0.05, 0.01, and 0.001) temperature decrease at same dosages. Fruits of A. barbata demonstrated significant pharmacological and antioxidant potential in both crude and fractionated extracts. Bangladesh Pharmaceutical Journal 29(1): 16-26, 2026 (January)